Biomechanical determinants of running economy - Fukuchi, C. A.; Stefanyshyn, D. J.; Wannop, J. W. (Journal of Sports Sciences, 2025)
Running economy (RE) defined as the submaximal rate of oxygen consumption during running, has been correlated with better performance. Biomechanical factors such as spatiotemporal parameters and lower extremity mechanics play a significant role in influencing RE. However, the relationship between RE and biomechanical variables in middle-distance running shoes is still unclear. In this study, twenty-one healthy male runners (age: 32.5 ± 5.6 years, height: 1.70 ± 0.10 m, body mass: 69.9 ± 7.3 kg) performed running trials on the treadmill. Physiological and biomechanical variables, including joint angles, moments, angular velocities, powers, ground reaction forces, and spatiotemporal parameters were analyzed. Multiple linear regression and backward stepwise regression analyses were employed to identify key biomechanical determinants of RE. The final regression model identified that the hip positive power, knee extension angular velocity, ankle plantarflexion angular velocity and negative power, and metatarsophalangeal extension angular velocity explained 73% of RE variability. Therefore, focus on optimizing these biomechanical variables, possible with specific shoe properties, could lead to enhanced RE in middle-distance running shoes.